Chronic Material Deprivation and Long-Term Poverty in Europe in the Pre-Crisis Period - Fotis Papadopoulos; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2016)
The paper examines the degree of overlap between people who experience chronic material deprivation and those who face long term income poverty (longitudinal poverty) in 22 EU countries for the period 2005-2008, using the longitudinal information of the EU-SILC. In order to approximate chronic material deprivation we use a three-step index of chronic cumulative disadvantage. In the first step, population members deprived in three domains of static material deprivation are identified. In the second step, the extent of cumulative disadvantage of these individuals is examined and, in the final step, persons suffering from chronic cumulative disadvantage over the period 2005-2008 are identified, by aggregating the information on static cumulative disadvantage in each year covered. Then, we examine the overlap between chronic material deprivation and (smoothed) longitudinal poverty. The results reveal considerable differences across EU countries regarding both the level and the structure of the population at high risk of chronic material deprivation and longitudinal poverty. Finally, each country's population is subdivided into mutually exhaustive and exclusive groups according to the characteristics of the population member, according to seven alternative criteria: Sex, age employment status and education level of the household's reference person, age and education of the individual and household type. The results of the analysis reveal a number of qualitative similarities and quantitative differences across EU member states. Nevertheless, in almost all countries under examination, lack of full employment by the individual or, especially, by the household's reference person, low educational qualifications, being a member of a lone parent household or living in a household headed by a woman or by a very young or, to a lesser extent, an elderly person, lead to high risks of chronic material deprivation as well as longitudinal poverty.
Keywords: I31; I32; J64; 330; chronic relative material deprivation; EU-SILC; Europe; income smoothing; consistent poverty; longitudinal poverty